2022
DOI: 10.33588/rn.7506.2022194
|View full text |Cite
|
Sign up to set email alerts
|

Dolor en el postoperatorio de cirugía cardíaca: bases neurobiológicas y tratamiento

Abstract: Introducción. A pesar de la evolución de las técnicas quirúrgicas, el dolor sigue siendo uno de los trastornos más frecuentes en el postoperatorio de la cirugía cardíaca (CCA), lo que condiciona la aparición de complicaciones en la fase aguda y el deterioro de la calidad de vida por la aparición de dolor crónico. En esta revisión narrativa pretendemos analizar los factores pronósticos de la aparición de dolor postoperatorio tras CCA, localizar y cuantificar la gravedad del dolor neuropático y dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
(81 reference statements)
0
1
0
Order By: Relevance
“…42 Van Gulik et al 30 demonstrated that remifentanil during cardiac anesthesia appears to be an independent predictor of chronic pain within 1 year after sternotomy. However, chronic postsurgical pain after thoracotomy can be multifactorial, and a growing number of studies have attempted to identify risk factors for its development, 41,43 but the quantification of pain is limited by subjective perception of patients. Persistent postsurgical pain may be somatic, visceral, or neuropathic.…”
Section: Discussionmentioning
confidence: 99%
“…42 Van Gulik et al 30 demonstrated that remifentanil during cardiac anesthesia appears to be an independent predictor of chronic pain within 1 year after sternotomy. However, chronic postsurgical pain after thoracotomy can be multifactorial, and a growing number of studies have attempted to identify risk factors for its development, 41,43 but the quantification of pain is limited by subjective perception of patients. Persistent postsurgical pain may be somatic, visceral, or neuropathic.…”
Section: Discussionmentioning
confidence: 99%